KNOWLEDGE, ATTITUDES AND PRACTICES OF FOOD HANDLERS IN FOOD SERVICES - Carla Ionara Xavier da Silveira Cardoso; Marcos Gilson Gomes Feitosa; Dinara Leslye Macedo e Silva Calazans (Universidade do Estado do Rio de Janeiro, 2018)
Aim: Assessing the level of knowledge, attitudes and practices of food handlers working in food services. Materials and Methods: Cross-sectional study conducted with food handlers from 15 food services: 75 individuals, in total. A questionnaire containing sociodemographic, as well as knowledge, attitudes and practices (KAP) evaluation questions was applied. The self-administered questionnaire comprised 30 questions about good food-handling practices. Scores equal to or higher than 70% were considered adequate to evaluate each block and the questionnaire as a whole. Data were analyzed in the SPSS software version 22. Results and Discussion: 64% of the herein evaluated food handlers performed commercial restaurant activities, 84% were women, and 52% had high school education. With respect to the KAP questions, the knowledge and attitude blocks recorded lower scores than the practice block. The mean score in the questionnaire was 54.9 ± 4.18. Failures in the understanding and knowledge about food handling may lead to lower awareness about proper handling procedures and result in false ideas about food safety. Conclusion: Food handlers presented food handling-knowledge deficiencies; therefore, it is necessary training them so they can aggregate information to improve their performance.  DOI: 10.12957/demetra.30528